PENGARUH PERSEPSI, MINAT, PERAN LINGKUNGAN, DAN PENGETAHUAN PERPAJAKAN MAHASISWA AKUNTANSI TERHADAP KEPUTUSAN PEMILIHAN BERKARIR DI BIDANG PERPAJAKAN - Rindiani, Devy; Srimindarti, Ceacilia (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This study aims to examine the effect of perceptions, interests, environmental roles, and tax knowledge of accounting students on the decision to choose a career in taxation. The population in this study were accounting students at Stikubank Semarang University and Diponegoro University Semarang. The sample in this study were accounting students at Stikubank Semarang University and Diponegoro University Semarang who had already taken taxation courses. The results of this study indicate that positive perceptions and interests are significant towards the decision to choose a career in the field of taxation. Unlike the case with the role of the environment and tax knowledge which is not significant to the decision to choose a career in the field of taxation.